Botulinum Toxin Treatment for Limb Spasticity in Childhood Cerebral Palsy - Pavone, Vito; Testa, Gianluca; Restivo, Domenico A.; Cannavò, Luca; Condorelli, Giuseppe; Portinaro, Nicola M.; Sessa, Giuseppe (Frontiers in Pharmacology, 2016)
CP is the most common cause of chronic disability in childhood occurring in 2–2.5/1000 births. It is a severe disorder and a significant number of patients present cognitive delay and difficulty in walking. The use of botulinum toxin (BTX) has become a popular treatment for CP especially for spastic and dystonic muscles while avoiding deformity and pain. Moreover, the combination of physiotherapy, casting, orthotics and injection of BTX may delay or decrease the need for surgical intervention while reserving single-event, multi-level surgery for fixed musculotendinous contractures and bony deformities in older children. This report highlights the utility of BTX in the treatment of cerebral palsy in children. We include techniques for administration, side effects, and possible resistance as well as specific use in the upper and lower limbs muscles.